"Not only at exclusion": the Picture of Nostalgia in Philip Larkin's Poetry - Masi, Jacopo (2021)
Critics of Philip Larkin’s poetry seem to be divided between those who consider it the expression of a profound nostalgic feeling and those who deny any trace of nostalgia in it, laying emphasis on the intellectual aloofness and ironic detachment of the poet’s stance. Seamus Heaney, for example, commenting on four of Larkin’s poems (“At Grass”, “MCMXIV”, “How Distant” and “The Explosion”), judged them “visions of ‘the spiritual, Platonic old England’”. A similar perspective can be found in Osterwalder’s essay on Larkin and Thwaite or in Brownjohn’s Philip Larkin (Longman, London, 1975), among others. On the contrary, Donald Davie, comparing Larkin to Betjeman, affirms that the main difference between the two poets lies in Betjeman being “the most nostalgic of poets, Larkin the least.” Drawing on Boym’s distinction between “restorative” and “reflective nostalgia” and using textual examples from a number of poems, my paper analyses the interplay between nostalgia, as a sentiment triggered by distance, and rhetoric distancing devices (irony in the first place) that creates an ambivalent emotional tension in which neither of the two poles is obliterated by the other.